2010
DOI: 10.1007/s00266-010-9502-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Outcomes Among Microtia Patients of Different Ages and Genders Before Ear Reconstruction

Abstract: Boys with microtia faced more psychological problems than girls. Their mental disorders apparently increased when they reached adulthood. The mothers of microtia patients endured more mental problems. Thus, this study provided a better understanding of the psychosocial morbidity experienced by microtia patients and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 25 publications
0
74
0
2
Order By: Relevance
“…13e15 It has been described that psychosocial problems begin in microtia patients around eight to ten years of age, consistent with the belief that the psychological issues become greater as the child enters school and enters adolescence. 16 It has been shown that the prevalence of mood disorders, including depression, interpersonal sensitivity/social difficulties, and hostility/aggression, increases with age in patients who have not had reconstructive surgery. 17 As a point of comparison, reviews of psychosocial functioning in children with cleft lip/palate have found generally adaptive adjustment and selfesteem, with specific concerns with behavioral problems, dissatisfaction with facial appearance, and some aspects of social functioning.…”
Section: Introductionmentioning
confidence: 99%
“…13e15 It has been described that psychosocial problems begin in microtia patients around eight to ten years of age, consistent with the belief that the psychological issues become greater as the child enters school and enters adolescence. 16 It has been shown that the prevalence of mood disorders, including depression, interpersonal sensitivity/social difficulties, and hostility/aggression, increases with age in patients who have not had reconstructive surgery. 17 As a point of comparison, reviews of psychosocial functioning in children with cleft lip/palate have found generally adaptive adjustment and selfesteem, with specific concerns with behavioral problems, dissatisfaction with facial appearance, and some aspects of social functioning.…”
Section: Introductionmentioning
confidence: 99%
“…There is an overall increased rate of depression and anxiety in microtia patients compared with a control cohort. 24,25 Studies have shown reduced psychological stressors after undergoing microtia reconstruction and overall patient satisfaction. 2628 Furthermore, a reconstructed auricle will permit retention of a hearing aid or glasses.…”
Section: Indications and Counselingmentioning
confidence: 99%
“…A silicon suction drain is placed for 2-3 days. Brent recommends allowing 3 months before proceeding to the next stage to allow wound healing to take place (Li et al, 2010).…”
Section: Brent's Techniquementioning
confidence: 99%